Microstructure study on optimization of high strength fly ash based geopolymer - Mohd Mustafa Al Bakri, Abdullah; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Mohamed, Bnhussain, Prof. Dr.; Khairul Nizar, Ismail, Assoc. Prof. Dr.; Rafiza, Abdul Razak; Zarina, Yahya (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/